The Impact of Hemorrhagic Shock on Lung Ultrasound–Induced Pulmonary Capillary Hemorrhage. (28th August 2020) - Miller, Douglas L.; Dou, Chunyan; Raghavendran, Krishnan; Dong, Zhihong
Abstract : Objectives: Lung ultrasound (LUS) exposure can induce pulmonary capillary hemorrhage (PCH), depending on biological and physical exposure parameters. This study was designed to investigate the variation in the LUS induction of PCH due to hemorrhagic shock, which itself can engender pulmonary injury. Methods: Male rats were anesthetized with isoflurane in air. Shock was induced by withdrawal of 40% of the blood volume and assessed by the blood pressure detected by a femoral artery catheter and by blood glucose tests. B‐mode ultrasound was delivered at 7.3 MHz with a low output (−20 dB) for aiming and with the maximal output (0 dB) for exposure. Pulmonary capillary hemorrhage was quantified by an assessment of comet tail artifacts in the LUS images and by measurement of PCH areas on the surface of fresh lung samples. Results: Tests without shock or catheterization surgery gave results for PCH similar to those of previous studies using different methods. Exposure before hemorrhagic shock gave a mean PCH area ± SE of 24.8 ± 9.2 mm 2 on the ultrasound scan plane, whereas exposure after shock gave 0 PCH ( P < .001; n = 7). Conclusions: The presence of hemorrhagic shock significantly reduces the occurrence of LUS‐induced PCH.